Fragments From Life of a Qadi: Mehmed (Muhamed) Seid-efendija Hajrić – Homarija - Omanović-Veladžić, Alma (Prilozi za orijentalnu filologiju, 2019)
In this paper, an attempt has been made to reconstruct the life of a qadi, who has performed the qadi service in several judgeships of the Bosnian Eyalet, based on the available resources, and belonged to the Bosniak elite of the time in which he lived and actively participated in various fields of cultural, social and political life. This qadi was Mehmed (Muhamed) Seid-efendija Hajrić – Homarija from Sarajevo, who, in addition to his usual qadi and administrativestate duties, as an educated and learned man, also dealt with some interesting events that entered his mecmu‘a and poems in the Ottoman-Turkish language. In the end, we brought records of how other people of his time had seen him, among whom there were also contradictory opinions about this person. In this paper, we used a prosopographic method, which in a special way illu minates the phenomena of social history that can not be perceived by some other method.